2016
DOI: 10.1177/0748730416668048
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Female Drosophila Sleep following Mating Are Mediated by SPSN-SAG Neurons

Abstract: Female Drosophila melanogaster, like many other organisms, exhibit different behavioral repertoires after mating with a male. These postmating responses (PMRs) include increased egg production and laying, increased rejection behavior (avoiding further male advances), decreased longevity, altered gustation and decreased sleep. Sex Peptide (SP), a protein transferred from the male during copulation, is largely responsible for many of these behavioral responses, and acts through a specific circuit to induce rejec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 57 publications
2
53
1
Order By: Relevance
“…We discover that both daytime and nighttime sleep are increased post-mating in tud progeny females without a germline, whereas nighttime sleep is decreased post-mating in control tud progeny females with a germline. This sleep result is distinct from previous studies that found daytime post-mating sleep decreased in all strains but white Berlin (Isaac et al 2010;Garbe et al 2016;Dove et al 2017). We find that the female post-mating preference for yeast-containing media is independent of presence of eggs and receipt of sperm.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…We discover that both daytime and nighttime sleep are increased post-mating in tud progeny females without a germline, whereas nighttime sleep is decreased post-mating in control tud progeny females with a germline. This sleep result is distinct from previous studies that found daytime post-mating sleep decreased in all strains but white Berlin (Isaac et al 2010;Garbe et al 2016;Dove et al 2017). We find that the female post-mating preference for yeast-containing media is independent of presence of eggs and receipt of sperm.…”
contrasting
confidence: 99%
“…Sleep: We examine differences in sleep post-mating, as to our knowledge, sleep has not been assayed in females lacking a germline (Table S1 for publication summary; for sleep statistical tests see Figure S6 and Table S5). Previous work has shown that mating results in decreased daytime sleep, across multiple strains, including CS, Oregon R, iso 31 , and w 1118 , but not white Berlin (see Table S1; Isaac et al 2010;Garbe et al 2016;Dove et al 2017). In female strains with a germline (CS, Berlin and tud/+), we confirm that CS has a significant post-mating reduction in daytime sleep, whereas Berlin had a significant increase in daytime sleep ( Figure S6A and B and Table S5).…”
Section: Female Genotype Impacts Gene Expression Changesmentioning
confidence: 97%
See 1 more Smart Citation
“…SP appears to be the molecular switch that changes the behavior of post-mated females by increasing locomotor activity and reducing sleep [33]. A similar response to mating by female D. melanogaster was also observed in other studies and in the related fruit fly D. suzukii, which also receives SP in the male seminal fluid [46,20,47]. showed that a 5-day enriched social experience amongst same and mixed sex adults can substantially increase the amount and quality of sleep of individuals compared to flies that have been deprived of any social interactions from eclosion [48].…”
Section: Introductionsupporting
confidence: 70%
“…3B) and the strong increase in micro-movements (Fig. 3C) are likely to represent an increase in food intake and egg-laying activity and may explain why such a strong decline in sleep amount was never identified using different tools (27,43,44). Interestingly, four-dimensional behavioural fingerprinting showed that the short sleep phenotype observed upon mating is qualitatively different from the one observed as natural variation in the CantonS population ( …”
Section: Qualitatively Different Types Of Short Sleeping Femalesmentioning
confidence: 99%